Venous thrombosis in children, adolescents and young adults with acute lymphoblastic leukemia receiving chemotherapy in the Republic of Belarus - V. V. Dmitriev; N. V. Migal; O. I. Bydanov; N. V. Lipay; E. V. Dmitriev (Онкогематология)
Objective: to clarify the conditions for the occurrence of thrombosis and assess the effect of anticoagulant therapy on the survival and outcome of thrombosis in children, adolescents and young adults with acute lymphoblastic leukemia (ALL) receiving program chemotherapy.Materials and methods. The study included 592 patients with ALL received program chemotherapy from 2008 to 2017 in the Belarusian Research Center for Pediatric Oncology, Hematology and Immunology (Minsk, Belarus). Of them, in 42 patients various localization venous thrombosis was detected at different therapy phase.Results. The cumulative detection rate of thrombosis was 7.5 ± 1.1 %. The use of pegelated asparaginase (PEG-asp) at a dose of 1000 IU/m2 in induction therapy increased the relative risk of thrombosis in the first 5 weeks of treatment by 3 times (relative risk 3.4; 95 % confidence  interval 0.98–11.9), compared to patients not receiving PEG-asp. The cumulative detection rate of thrombosis in patients with the post-induction L-asparaginase (L-asp) 25,000 IU/m2 regimen was 14.7 ± 2.6 %, which was higher (p = 0.0536) than when using L-asp in other dosing regimens. In addition to ALL as the main disease, taking chemotherapy drugs, other risk factors for thrombosis (thrombophilia, the presence of antiphospholipid antibodies, a decrease of natural anticoagulants activity) in various combinations were in half (23 of 42) patients with venous thrombosis. Therapeutic dose of low molecular weight heparins (LMWH) 150–200 IU/kg received 30 patients. Reduced for the period of thrombocytopenia from 100 to 35 × 109/L for up to 4 weeks, a daily dose of LMWH was received by 12 patients. The dose of LMWH was reduced in proportion to the blood platelets count. After the recovery of the platelet count of more than 100 × 109/L, patients continued treatment of LMWH in a daily dose of 150–200 anti-Xa IU/kg. Reducing of LMWH dose during thrombocytopenia period did not affect the outcome of thrombosis (χ2 = 0.494; p = 0.78). Among 42 patients with thrombosis, 38 completed maintenance therapy, eventfree survival was 83.0 ± 8.0%, which did not differ (p = 0.654) from that (81.0 ± 2.0 %) in patients without thrombosis. Conclusion. The presence of venous thrombosis with the use of LMWH as antithrombotic therapy did not lead to a decrease in the event-free survival of ALL patients, compared with those without thrombosis. Reducing the therapeutic dose of LMWH did not affect the outcome of thrombosis in the analyzed groups.